Exploring the Feasibility of a Caregiver Burden-Mastery Hybrid Assessment Tool With Decision Matrix in a Memory Clinic: A Multimethod Study - Ee Yuee Chan RN, PhD, MSc, MN, BN; Zhi Lei Ong BA; George Frederick Glass RN, MSc, BN (Hons); Siew Ling Ang RN; Jun Pei Lim MMed, MBBS; Noorhazlina Binte Ali MMed, MBBS; Wee Shiong Lim MD, MMed, MHPEd, MBBS (SAGE Open Nursing)
Introduction Family members caring for a person living with dementia (PWD) can experience caregiver burden, leading to psychological distress if unmanaged. It's essential for healthcare professionals, especially nurses to identify caregivers at risk of stress and depression, triggering prompt management during their contact with caregivers of PWD. The study team developed an evidence-based caregiver burden-mastery hybrid assessment and intervention decision matrix (CHAT-MI) for caregivers of PWD and examined its feasibility of use. Objective To determine the feasibility and usability of implementing the CHAT-MI assessment-decision matrix tool in an outpatient setting in Singapore. Methods CHAT-MI was developed through earlier research, research evidence, clinical guidelines, and expert opinion. A multimethod study was conducted in a Singapore outpatient memory clinic from November 2020 to January 2021. Caregivers of PWD who attended the clinic self-administered the assessment tool to determine their burden and personal mastery levels. Clinicians used a decision matrix to guide interventions based on the assessments. Feedback was gathered from both caregivers and clinicians through surveys and semistructured interviews. Results Thirty-four caregivers and six clinicians participated in the study. Caregivers found the burden-mastery assessment tool relatively easy to use and understand and helpful. Clinicians found the assessment-decision matrix tool acceptable, feasible, and useful, enhancing standard care by providing insights into caregivers’ current coping capabilities. Clinicians shared that junior clinicians could benefit from CHAT-MI to better detect caregiving stress and deliver interventions. Nevertheless, more can be done to train clinicians in the understanding of the concept of mastery (i.e., perceived control over life events) to help clinicians better engage and support caregivers. Conclusion CHAT-MI was found to be relatively brief and can aid the outpatient clinic setting. This suggests that such an evidence-based assessment cum intervention can be considered for use in a real-world clinical setting to aid both caregivers and clinicians.